"I am a father now": Colonial paternalism and oedipal typicality in Shaun Johnson's The Native Commissioner. (June 2017) - Emmett, Christine
This article considers the prevalence and dynamics of colonial paternalism and oedipal typicality as they operate within Shaun Johnson's novel, The Native Commissioner (2006). Therefore, the article explicates how Freud's oedipal theory can, read within its historical context, contribute and serve as a tool to elucidate colonial discourses. It also indicates the prevalence of colonial paternalism, not merely through the South African Union government (1910–1961) and apartheid, but as I will argue, within post-apartheid South Africa. Johnson's novel, which presents a father–son narrative, interfaces with colonial paternalism through the father, George Jameson, and his role as a Native Commissioner. Through an analysis of the ideological assumptions underlying George's identity as a father (and associated notions of husbandry, gardening, and cultivation), the shared ideological basis of his career as a Native Commissioner and his seemingly neutral role as a patriarch is highlighted. The article then considers how oedipal dynamics structure the novel's focus on paternalism. Through an analysis of George's failure as a patriarch and the psychically invested nature of the narrative, we encounter the concomitant anxiety of the son-as-narrator. This anxiety manifests itself in the oedipal mechanics of castration anxiety, rivalry, and identification as originally explicated by Freud. Through these mechanics, the power of the son-as-narrator is emphasized as the father dies and the son identifies with the father's power. The remainder of the article re-contextualizes these findings within the novel's reception by South African audiences. The novel's popularity suggests that colonial paternalism remains a discourse that still has significant purchase for white South Africans even amid calls to identities based on equality and multiculturalism.